Emerging Roles of Cyclophilin A in Regulating Viral Cloaking - Mamatis, John E.; Pellizzari-Delano, Isabella E.; Gallardo-Flores, Carla E.; Colpitts, Che C. (Frontiers in Microbiology, 2022)
Cellular cyclophilins (Cyps) such as CypA have emerged as key players at the virus-host interface. As host factors required for the replication of many unrelated viruses, including human immunodeficiency virus (HIV), hepatitis C virus (HCV) and coronaviruses (CoVs), Cyps are attractive targets for antiviral therapy. However, a clear understanding of how these viruses exploit Cyps to promote their replication has yet to be elucidated. Recent findings suggest that CypA contributes to cloaking of viral replication intermediates, an evasion strategy that prevents detection of viral nucleic acid by innate immune sensors. Furthermore, Cyps are emerging to have roles in regulation of cellular antiviral signaling pathways. Recruitment of Cyps by viral proteins may interfere with their ability to regulate these signaling factors. Consistent with disruption of viral cloaking and innate immune evasion, treatment with Cyp inhibitors such as cyclosporine A (CsA) restores antiviral innate immunity and induces expression of a subset of antiviral genes that restrict viral infection, which may help to explain the broad antiviral spectrum of CsA. In this review, we provide an overview of the roles of CypA in viral cloaking and evasion of innate immunity, focusing on the underlying mechanisms and new perspectives for antiviral therapies.